Tooth Lengths of the Permanent Upper Incisors in Patients with Cleft Lip and Palate Determined with Cone Beam Computed Tomography. (January 2013) - Zhou, Weihua; Li, Weiran; Lin, Jiuxiang; Liu, Denggao; Xie, Xiaoyan; Zhang, Zuyan
Objective: To measure the tooth lengths of fully developed permanent upper incisors and to qualitatively evaluate the root shapes of the incisors in patients with cleft lip and palate (CLP). Design: Cross-sectional, noninterventional, case-control imaging study. Setting: Hospital and Stomatology Unit of Peking University, Beijing, China (institutional tertiary care). Participants: Sixty consecutive nonsyndromic CLP patients (including 40 unilateral [UCLP] and 20 bilateral [BCLP]), and 53 age- and sex-matched controls were selected for this study. Main Outcome Measure: Crown heights and root lengths of permanent upper incisors were measured from cone beam computed tomography scans, and the root shapes of upper incisors were evaluated. Results: Compared with controls, the crown heights of upper incisors in CLP patients were reduced by 9.7% to 22.5% ( p < .05), and the root lengths were reduced by 15.8% to 31.7% ( p < .05). BCLP patients had greater reductions than the UCLP cases ( p < .05). There were no significant differences between incisors and their antimeres in controls and BCLP patients. However, measurements on the cleft side in UCLP patients were lower than those of the noncleft side ( p < .05). The prevalence of atypical root shape was higher in CLP than in the control group ( p = .002); of these, 83.3% (30/36) occurred in central incisors near the cleft. Conclusion: The permanent upper incisors in nonsyndromic CLP patients are underdeveloped. Incisor developmental deficiency was greater in teeth adjacent to the cleft.